Teachers’ Patterns of Management of Conflicts With Students: A Study in Five European Countries - Maria Clelia Zurlo; Federica Vallone; Elena Dell’Aquila; Davide Marocco (Europe's Journal of Psychology, 2020)
The present study proposed an application of the Rahim’ Model of Conflict Management, and aimed to explore the styles of handling interpersonal conflicts with students adopted by teachers from five European countries (Italy, Spain, Germany, Belgium, Austria), identifying specific patterns and evaluating potential differences according to teachers' Gender, Age, Working Seniority and Country of belonging. Overall, 589 secondary school teachers completed a questionnaire consisting of Socio-demographic characteristics and the Rahim Organizational Conflict Inventory-II (ROCI-II, Form B). Non-hierarchical k-means cluster analysis was employed to derive patterns of conflict management, identifying four patterns labelled as Multi-strategic and Engaged, Multi-strategic and Solution-Oriented, Control-Oriented and Avoidant, and Mediating. Significant differences between countries were found in the numbers of teachers grouped across the four patterns. Findings identified stable and meaningful patterns for evaluating teachers' styles of management of interpersonal conflicts with students and for promoting teachers’ effectiveness in conflict management in the European school context.